Drilling and Production-Equipment, Methods and Materials - Ability of Drilling Mud to Lift Bit Cuttings - H. N. Hall; Howard Thompson; Frank Nuss (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1950)
Removal of bit cuttings is an important function of drilling muds. In an effort to obtain better understanding of the factors influencing the removal of cuttings, an extensive series of laboratory tests were made in which slip velocities of various sizes and shapes of particles were measured in muds of different physical properties. Empirical equations were then derived from these experimental data. These equations show that slip velocity is dependent on cutting size and shape, mud flow constants, and flow state of the mud. Applicability of these equations for field use is demonstrated by comparing computed slip velocities with slip velocities obtained from field tests. Drilling muds have many functions, but perhaps the most important is the removal of bit cuttings from the well. In a 10,000-ft well, the weight of rock which is drilled and must be carried to the surface is over 150 tons. In addition to this, the mud must remove any sloughings from the well bore. Failure of the mud to promptly remove either bit cuttings or sloughs from the well bore causes re-drilling and excessive wear on bit teeth, slows down drilling rate thereby increasing well costs, and greatly increases possibilities for stuck drill pipe when circulation is stopped for any length of time. Drilling muds lift bit cuttings to the surface by means of the upward velocity of the drilling mud in the annulus. Because a density difference exists between the rock being drilled and the drilling mud, there is a difference between mud velocity and the rate of bit cutting travel, called the net rise velocity. To evaluate the ability of any type of drilling mud in respect to lifting cuttings, some method must be known for predicting the rate of fall of cuttings through mud traveling upwards in the annulus. Equations for the rate of fall of particles through a true fluid have been satisfactorily determined by several authors. 1-6 Since drilling muds are not true fluids, but obey the laws of Bing-ham,7 it should not be expected that equations for rate of fall of cuttings in a true fluid would be applicable to plastic fluids such as drilling muds. Several authors have attempted to compute cutting slip velocities in muds using a viscosity value obtained with a Stormer viscosimeter; however, unsatisfactory results were obtained. Pigott8 took cognizance of the phenomenon of variation of viscosity with velocity in laminar Row, and calculated laminar slip velocities using a variable viscosity with Stokes law, and turbulent slip velocities using Rittingers law. Drilling muds obey the laws of plastic flow which involve factors not affect-